INSPECTION OF THE ADEQUACY OF CLOSED-DRAIN AND OPEN-DRAIN SYSTEMS USING HYDRAULIC ANALYSIS FOR AGING OFFSHORE PLATFORMS - mutadi, mutadi (Institut Teknologi Sepuluh Nopember, 2025)
Aging offshore platforms require a reliable drainage system to ensure safety and operational efficiency. This study aims to analyze the adequacy of the closed drain and open drain systems on a 24-year-old offshore platform that is scheduled for redevelopment. The methodology employed involves hydraulic analysis, considering fluid production rates and drainage system design data based on API 14E and GPSA (2004) standards. The collected data included channel cross-section dimensions, flow rates, and fluid characteristics to calculate the system's capacity. The analysis showed that the 4-inch header pipe was adequate to accommodate a closed drain flow rate of 167.4 BPD and an open drain flow rate of 1.63 BPD. The Slop Tank (Platform X-T-26), with a geometric volume of 54 ft3, was also adequate to contain the maximum drainage volume of 15.23 ft3 from the Vertical Test Separator. This study also identified several critical points that require periodic monitoring to prevent blockages and performance degradation. This study emphasizes the importance of periodic inspections to assess the adequacy of drainage systems on aging offshore platforms to ensure safety and operational efficiency after redevelopment. It also provides preventive maintenance recommendations to extend the system's lifespan.